Reconciling the Universal Goals of Education with Diversity: An Examination of Two Alternative Schools in Toronto - Buckley, Katie (Université d'Ottawa | University of Ottawa, 2014)
Aboriginal and visible minority students consistently lag behind their Caucasian counterparts in their academic achievements in Canadian public schools. The dropout rates of Aboriginal population ranged between 70 per cent in the 1980s to 40 per cent in the early 200 while the dropout rates of the Black populations have remained relatively static at 40 per cent since the 1990s. Institutionalized racism and the delivery of a Eurocentric curriculum that nullifies the experience and knowledge of non-European peoples have been identified by a number of scholars as key impediments to the academic success of non-White students. In cert instances, the establishment of alternative schools catering to the needs of a specific populatio has been adopted as a solution to these problems. This project will examine the establishment of two alterative schools in Toronto: Wanderi Spirit Survival School for Aboriginal students founded in 1976, and the Africentric Alternativ School of Toronto for Black students founded in 2008, to determine the extent to which they a congruent with existing multicultural theories. To this end, the project will make use of three highly influential theories pertaining to the reconciliation of diversity within liberal democrati societies advanced by Charles Taylor, Will Kymlicka, and Brian Barry. It will then consider th ways in which normative discourse can influence public policy and subsequently speculate on how the justifications for policy instruments can change over time. The project concludes that establishment of alternative schools such as Wandering Spirit Survival School and the Africen School of Toronto are imperfectly aligned with current conceptions of multicultural theory.